Not the final diagnosis: from Addison's disease to POEMS syndrome: a case report and literature review. Issue 12 (December 2021) - Xie, Xiaoxi; Li, Rao; Lu, Yongxia; Li, Xuan; Kuang, Pu; Wang, Chunhui; Tong, Nanwei; Lü, Qingguo
We report the case of a 47-year-old male patient with pigmentation of the head, face and hands, who was initially diagnosed as having primary adrenal insufficiency (Addison's disease). Laboratory testing, imaging and physical examination revealed subclinical hypothyroidism, high circulating prolactin and oestradiol concentrations, gynaecomastia, lymphadenopathy, splenomegaly and weakness of both lower limbs. These findings led us to consider whether a single or multiple diseases were present in this patient. Indeed, Addison's disease can represent one aspect of a wider systemic disease. Therefore, we performed further examinations, and found high serum M protein (5.1%) and vascular endothelial growth factor [1005.30 pg/mL (normal range 0 to 142 pg/mL)] concentrations. As a consequence, we diagnosed polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin changes (POEMS) syndrome. Consequently, when a single disease cannot fully explain the multiple symptoms and signs of one patient, clinicians should consider the possibility of the presence of a wider syndrome and undertake more detailed diagnostic testing.